A Critical Assessment of National Rural Health Mission (NRHM) for Rural Health Security in Uttar Pradesh - Ram Jiyawan , O.P.Mishra and Sharada, (Indian Journal of Extension Education, 2017)
India has registered significant progress in improving health condition of the people over the last few decades. In spiteof the progress made, a high proportion of the population, especially in rural areas, continues to suffer and die frompreventable diseases, pregnancy and child birth related complications as well as malnutrition. National Rural HealthMission (NRHM) has launched in 2005 to improve the health system and the health status of the rural people.However, studies have revealed that the lack of awareness about this programme, depriving the potential benefits tothe people. So the present study entitled “National Rural Health Mission (NRHM) for rural health security: a criticalassessment” was undertaken to assess the programme effectiveness in terms of peoples' awareness, participation,satisfaction and constraints faced by them in harnessing the benefits from the programmes. The study was conductedin Kashi Vidyapeeth block of Varanasi district of Uttar Pradesh. The findings of the study revealed that 66.67% ofrespondents has medium level of awareness and 55.83 per cent of the respondents had expressed their satisfactionabout the services rendered by NRHM.